2022
DOI: 10.3389/fonc.2022.846497
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Long Non-Coding RNA GAS5 in Malignant Tumors

Abstract: With completing the whole genome sequencing project, awareness of lncRNA further deepened. The growth arrest-specific transcript 5 (GAS5) was initially identified in growth-inhibiting cells. GAS5 is a lncRNA (long non-coding RNA), and it plays a crucial role in various human cancers. There are small ORFs (open reading frames) in the exons of the GAS5 gene sequence, but they do not encode functional proteins. In addition, GAS5 is also the host gene of several small nucleolar RNAs (snoRNA). These snoRNAs are bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…This was similar to previous reports that curcumin and lncRNA GAS5 can promote cell survival [20][21][22]. Expression levels of GAS5 in various tumors have been studied [16]. However, adding curcumin while overexpressing the lncRNA GAS5 made this effect disappear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was similar to previous reports that curcumin and lncRNA GAS5 can promote cell survival [20][21][22]. Expression levels of GAS5 in various tumors have been studied [16]. However, adding curcumin while overexpressing the lncRNA GAS5 made this effect disappear.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, highly expressed GAS5 is not only associated with an increased risk of IS but also promotes neuronal apoptosis after cerebral infarction [14,15]. GAS5 plays a critical role in various human cancers [16]. However, the effect of curcumin on lncRNA GAS5 is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…They found that negative pressure treatment after M. tuberculosis infection promoted macrophage polarization to proinflammatory M1 phenotype by regulating the long noncoding RNA XIST/micro-RNA-125b-5p/A20/nuclear factor- κ B axis [ 38 ]. Most transcripts of the human genome sequence are composed of noncoding RNAs, one of which is long noncoding RNA [ 39 ]. Although several long noncoding RNAs related to macrophages have been reported in recent years, many long noncoding RNAs related to macrophages are yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In the splice events observed, most spliced genes were lncRNAs SNHG2 (GAS5) and SNHG17, considering its non-coding function was an interesting finding. Splice forms alter the oncogenic and tumour role of GAS5 in malignant tumours ( Lin et al, 2022 ), and the role of non-coding RNA, SNHG17 in ovarian cancer needs to be investigated. ADAM15 splice events showed retention of residues Y715 and Y735 of the cytoplasmic tail, to facilitate motility and in turn proliferation.…”
Section: Discussionmentioning
confidence: 99%